2018
DOI: 10.1353/pla.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

Zines for Teaching: A Survey of Pedagogy and Implications for Academic Librarians

Abstract: Zines have begun to gain a place in higher education as pedagogical tools studied or made by students, and many academic libraries maintain zine collections. The library literature reveals little about how nonlibrarian faculty use zines in their classrooms. This paper describes the results of a survey of faculty from a range of academic disciplines and professions who teach with zines and other booklet forms. Survey results reveal the extent to which faculty zine pedagogies include collaboration with librarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Zines have value in art and design libraries collections particularly as documents representing the work of artists who identify as queer, feminist, or disabled as well as providing access to work from artists from Africa, Asia, and other parts of the world, generally not well represented in art collections (Moran 2018). Art and design libraries collect zines as a form of artist self-publishing and as art objects worthy of study in their own right; it is not uncommon for zines to be produced by established artists (Thomas 2009) and have been described as "a punk second-cousin to Artists' Books" (Hays 2020). Art institutions in the United Kingdom that hold zine collections include the Tate, the London College of Communications, Glasgow School of Art, the University for the Creative Arts, and the Stuart Hall Library.…”
Section: History and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Zines have value in art and design libraries collections particularly as documents representing the work of artists who identify as queer, feminist, or disabled as well as providing access to work from artists from Africa, Asia, and other parts of the world, generally not well represented in art collections (Moran 2018). Art and design libraries collect zines as a form of artist self-publishing and as art objects worthy of study in their own right; it is not uncommon for zines to be produced by established artists (Thomas 2009) and have been described as "a punk second-cousin to Artists' Books" (Hays 2020). Art institutions in the United Kingdom that hold zine collections include the Tate, the London College of Communications, Glasgow School of Art, the University for the Creative Arts, and the Stuart Hall Library.…”
Section: History and Contextmentioning
confidence: 99%
“…The zine format and open brief allow students to approach their introduction to academic writing in a way that encourages creativity and an unrestricted definition of what constitutes fashion discourse. There is some discussion of the effectiveness of zine making as a pedagogical tool in the literature, as using zines as a teaching tool is becoming increasingly common in art and design courses, including fashion design, but more commonly in art history, graphic design, photography, and communication design courses (Thomas 2018). Creasap (2014) found that the informal nature of the publications provided an unintimidating way of introducing students to academic work and that they responded well to the materiality of a zine, reporting that it made their ideas and contributions feel more substantial.…”
Section: Fashion Students Using and Making Zinesmentioning
confidence: 99%
“…The zine provides readers with a visual and tangible component to exercises that can be taken home and worked on independently. Rooted as a medium that arose to disperse information in a grassroots fashion, early zine creators worked independently of big publishing companies (Thomas 2018), a content-creation approach that echoes the current work of indie podcasters, who often work against the grain of big syndicated media. The zine proved to be a highly successful teaching tool within the PTP context, showing that "sixty-four percent of .…”
Section: The Preserve This Podcast Podcast and Zinementioning
confidence: 99%
“…Making has emerged as a form of critical pedagogy that supports active and participatory learning in higher education environments through the construction and sharing of something produced or created, often located in technology rich spaces (Blikstein, 2018;Bullock & Sator, 2015;Cohen, Huprich, Jones, & Smith, 2017). Many universities are investing in makerspaces and digital labs, supported by technology-led pedagogical innovations that can be used to connect students within and between disciplines, facilitating making and inspiring creative approaches to thinking by using digital technologies (such as 3D printers and drones) and more traditional maker forms and tools (such as Lego, DIY art or crafting) (Barrett et al, 2015;Moorefield-Lang, 2014;Thomas, 2018). The commonalities between the development and design of makerspaces and making as a form of teaching, learning and assessment are well explored in the literature on STEM education, both at University level and within secondary and primary schools (Barniskis, 2014;Barton, Tan, & Greenberg, 2016;Kalil, 2013).…”
Section: Introductionmentioning
confidence: 99%